Terrain Effect on Provincial PM2.5 Concentrations in South Korea 시도별 PM2.5 농도에 대한 지형효과 분석 - Jeong, Seongeun; Kang, Yoon Hee; Kim, Eunhye; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2024)
In this study, we investigated the terrain effect on PM2.5 concentrations across provinces in South Korea, focusing on the winter season, when PM2.5 levels typically increase. South Korea’s terrain, characterized by lower elevations in the west and higher elevations in the east, can significantly influence PM2.5 concentrations during the winter when prevailing winds are northwesterly. We employed the Community Multiscale Air Quality model coupled with the Weather Research and Forecasting model to simulate two scenarios: one with actual terrain heights and another with terrain flattened to 50 meters. The terrain affected dispersion and transport of air pollutants, leading to changes in PM2.5 concentrations across provinces, ranging from -7.6%~3.0%. Specifically, PM2.5 concentrations increased in northwestern provinces, such as the Seoul Metropolitan Area, while they decreased in southeastern provinces. The terrain effect on the local emissions impact (LEI) of PM2.5 concentrations in South Korea ranged from -11.3% to 6.3%, which was relatively more significant compared to the impact of long-range transport (LTI; -8.7% to 2.3%). However, in terms of absolute concentration changes, the LEI varied from -1.1 μg/m3 to 0.6 μg/m3, while the LTI ranged from -1.8 μg/m3 to 0.6 μg/m3, indicating that the LTI had a greater overall impact under the given conditions during the study period. Interestingly, in some provinces, PM2.5 concentrations decreased despite reduced ventilation. These results suggest that terrain plays a crucial role not only in the dilution and dispersion of locally emitted air pollutants but also in the transport of both transboundary and inter-provincial air pollutants. By hindering the northwesterly-to-southeasterly transport, particularly on elevated PM2.5 days (>35 μg/m3), the terrain in South Korea reduced the nation-wide, population-weighted PM2.5 concentration by 16%. Considering the decrease in LTI, and as the LEI becomes more significant in the future, understanding the role of terrain will be crucial for effectively reducing PM2.5 levels and minimizing human exposure.
Keywords: Dispersion and transport; Local emissions impact; Long-range transport impact; Population exposure; Terrain effect